PEDAGOGICAL-PSYCHOLOGICAL MECHANISMS OF DEVELOPING PEDAGOGICAL CULTURE - Nasimova Nasiba Djurakulovna (Bright Mind Publishing, 2025)
This article analyzes the methods of developing pedagogical culture in future teachers based on a competency-based approach, the structure and levels of pedagogical culture, and the requirements for a modern teacher.
Keywords: Competence, teacher, culture, method, approach, time, demand, development.